THE INFLUENCE OF WORK ENVIRONMENT, WORK DISCIPLINE, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT CV. FALDI ADVERTISING - Fahmi Sulaiman; Jihan Sulaiman (Smart Education, 2025)
Abstract: This study aims to determine and analyze the partial influence between the work environment on the performance of CV. Faldi Advertising employees, to determine and analyze the partial influence between work discipline on the performance of CV. Faldi Advertising employees, to determine and analyze the partial influence between work motivation on the performance of CV. Faldi Advertising employees, to determine and analyze the simultaneous influence between the work environment, work discipline and work motivation on the performance of CV. Faldi Advertising employees. This research is a quantitative research type, where the procedure used in this study is a correlational model.The sample in this study was all permanent employees at CV. Faldi Advertising, totaling 35 people. Simultaneously, the three independent variables significantly influence the performance variable because the significance value is smaller than 0.05. The Adjusted R Square value in the table above is 0.819 or 81.9%. This condition explains that 81.9% of the work environment, work discipline, and work motivation variables have a significant effect on the performance of CV. Faldi Advertising employees. The remaining 18.1% is influenced by other variables not examined in this study. This means that of the many factors supporting the performance of CV. Faldi Advertising employees, the work environment, work discipline, and work motivation factors have the most influence on performance, namely 81.9%.Â Keywords: The Influence of Work Environment, Work Discipline, Work Motivation, Employee Performance.